Physicians’ attitudes toward hypnotics for insomnia: A questionnaire-based study - Takeshima, Masahiro; Aoki, Yumi; Ie, Kenya; Katsumoto, Eiichi; Tsuru, Eichi; Tsuboi, Takashi; Inada, Ken; Kise, Morito; Watanabe, Koichiro; Mishima, Kazuo; Takaesu, Yoshikazu (Frontiers in Psychiatry, 2023)
Benzodiazepines and non-benzodiazepines are still widely prescribed despite safety concerns and the introduction of novel hypnotics (orexin receptor antagonists [ORA] and melatonin receptor agonists [MRA]), which may be influenced by physicians' attitudes toward hypnotics. A questionnaire survey was administered to 962 physicians between October 2021 and February 2022, investigating frequently prescribed hypnotics and the reasons for their selection. ORA were the most frequently prescribed at 84.3%, followed by non-benzodiazepines (75.4%), MRA (57.1%), and benzodiazepines (54.3%). Compared to non-frequent prescribers of hypnotics, a logistic regression analysis showed that frequent ORA prescribers were more concerned with efficacy (odds ratio [OR]: 1.60, 95% confidence interval [CI]: 1.01–2.54, p=0.044) and safety (OR: 4.52, 95% CI: 2.99–6.84, p<0.001), frequent MRA prescribers were more concerned with safety (OR: 2.48, 95% CI: 1.77–3.46, p<0.001), frequent non-benzodiazepine prescribers were more concerned with efficacy (OR: 4.19, 95% CI: 2.91–6.04, p<0.001), and frequent benzodiazepine prescribers were more concerned with efficacy (OR: 4.19, 95% CI: 2.91–6.04, p<0.001) but less concerned with safety (OR: 0.25, 95% CI: 0.16–0.39, p<0.001). This study suggested that physicians believed ORA to be an effective and safe hypnotic and were compelled to prescribe benzodiazepine and non-benzodiazepine frequently, choosing efficacy over safety.